PERANCANGAN SISTEM INFORMASI AKUNTANSI BEBASIS APLIKASI PADA BUMDES BATULILIH DESA NYURLEMBANG - Farha Farha; Agus Khazin Fauzi; Komariyuli Anwariyah; Septia Ningsih (Komunitas Manajemen Kompetitif, 2026)
This study aims to design an application-based accounting information system for the Bumdes Batulilih, The study used a descriptive method. The results indicate that an application-based accounting information system can be implemented in Bumdes. The use of an application-based accounting information system simplifies and accelerates bookkeeping, and the resulting financial reports are more transparent and accountable.